Mobile Energy Storage Systems for Benefit Maximization in Resilient Smart Grids - Alshaal, Dima (2025)
A Master of Science thesis in Electrical Engineering by Dima Alshaal entitled, “Mobile Energy Storage Systems for Benefit Maximization in Resilient Smart Grids”, submitted in April 2025. Thesis advisor is Dr. Mostafa Shabaan and thesis co-advisor is Dr. Mahmoud Ibrahim. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).